Adaptive Coding - Ridderinkhof, K. Richard; Wery P. M. van den Wildenberg (Science (American Association for the Advancement of Science), 2005)
A century ago, psychologists considered cognitive control to be a major player in decision-making. Yet, the study of how perception and action are mediated by instructions and intentions entered a twilight zone during the middle part of last century as behaviorists turned their backs on mental processes that they could not directly observe. Now, there is a resurgence of interest in understanding how the human brain regulates the flow of information to achieve intended goals that coincided with methodological innovations such as functional magnetic resonance imaging and electrical recordings from single neurons. Ridderinkhof and van den Wildenberg discuss Machens et al and Brown and Braver's studies that were inspired by the notion that neurons in the frontal region of the brain may dynamically and adaptively switch between multiple functions rather than statically accomplishing preset tasks.